PENGARUH STORE ATMOSPHERE DAN KUALITAS PRODUK TERHADAP NIAT BELI ULANG DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI (Survei Pada Konsumen Marakez Café di Surakarta) - Dita Rahmawati; Marjam Desma Rahadhini; Sumaryanto Sumaryanto (Universitas Slamet Riyadi, 2020)
This research was conducted on consumers Marakez Café in Surakrta, the type of data used is qualitative and quantitative data. Data sources used are secondary and primary data. The entire population in this study are all Marakez Café consumers whose numbers cannot be known. The sample used in this study was taken as many as 100 respondents. The sampling technique is done by using nonprobability sampling using purposive sampling method. In this study shows that store atmosphere and product quality significantly influence consumer satisfaction. Variable store atmosphere, product quality and customer satisfaction have a significant effect on repurchase intentions. The sobel test results in this study indicate that store atmosphere and product quality influence repurchase intentions with customer satisfaction as a mediating variable.